RAP Tag and PMab-2 Antibody: A Tagging System for Detecting and Purifying Proteins in Plant Cells - Miura, Kenji; Yoshida, Hideki; Nosaki, Shohei; Kaneko, Mika K.; Kato, Yukinari (Frontiers in Plant Science, 2020)
An affinity tag system requires both high affinity and specificity. The RAP tag epitope DMVNPGLEDRIE, derived from rat podoplanin (PDPN), is specifically recognized by PMab-2 monoclonal antibodies in rats. Here, we demonstrated that high levels of PMab-2 can be produced in Nicotiana benthamiana and plant-derived PMab-2 possesses similar activity to CHO-derived PMAb-2, and the RAP tag presents a useful tagging system for detecting and purifying proteins from plant cells. The heavy chain of PMab-2 fused with KDEL, an endoplasmic reticulum retention sequence, and the light chain of the antibody were introduced into N. benthamiana by agroinfiltration. The expression of PMab-2 peaked four days after agroinfiltration, and approximately 0.3 mg/g fresh weight of the antibody was accumulated. After purification, the plant-derived PMab-2 successfully recognized rat PDPN expressed in CHO-K1 cells, and exhibited almost the same binding activity as CHO-derived PMab-2. The RAP-tagged proteins expressed in plant cells were specifically recognized by PMab-2. These results indicate that PMab-2 can accumulate at high levels in N. benthamiana and is easily purified, and that the RAP tagging system presents a useful tool for detecting and purifying proteins of interest in plant cells.